Supplementation with partially hydrogenated oil in grazing dairy cows in early lactation - Schroeder, G. F. (2002)
Effects of partially hydrogenated oil on performance, loss of body weight and body condition score, and blood metabolite and hormone concentrations were evaluated in 37 multiparous Holstein cows in grazing conditions during the first 100 d of lactation. Six additional Holstein cows, each fitted with a ruminal cannula, were allocated to a replicated 3 x 3 Latin square to evaluate effects of supplemental fat on rumen environment and pasture digestion. All cows grazed mixed pastures based on alfalfa (Medicago sativa) and orchardgrass (Dactylis glomerata L.) and received 5.4 kg/d of a basal concentrate to which 0, 0.5, or 1 kg/cow per day of partially hydrogenated oil (melting point 58 to 60 degrees C) containing 30.3, 34.9, 21.8, and 3.3% of C16:0, C18:0, C18:1, and C182, respectively, was added. Feeding 1 kg/d of supplemental fat increased fat-corrected milk from 23.4 to 26.3 kg/d, milk fat content from 3.44 to 3.78%, and milk fat yield from 0.87 to 1.03 kg/d compared to control. Milk protein percentage and yield were not affected. Cows fed 1 kg/d of fat increased the content and yield of C16:0 and C18:0 in milk compared with cows fed no added oil. Dry matter intake (DMI) from pasture decreased from 17.8 kg/d for control cows to 13.6 kg/d for cows fed 1 kg of oil, whereas DMI from concentrate was higher for cows fed 1 kg/d of fat (6.0 kg/d) than for controls (5.2 kg/d). Supplemental fat did not affect total dry matter or estimated energy intake and did not change losses of body weight or body condition scores. Plasma concentrations of nonesterified fatty acids, insulin, somatotrophin, and insulin-like growth factor-I did not differ among treatments. Concentration of plasma triglycerides was lowered from 318.5 to 271.2 mg/dl, whereas plasma cholesterol was elevated from 185.0 to 235.8 mg/dl in cows receiving 1 kg/d of supplemental fat compared with controls. Responses to lipolytic or insulin challenges were not affected by feeding oil. Supplemental fat did not affect the digestion of pasture fiber. The addition of energy in the form of partially hydrogenated fat to early lactation dairy cows fed primarily on pasture increased the yield of fat-corrected milk and milk fat content when it represented about 11% of the total metabolizable energy requirement of cows, without affecting milk protein content. The partial hydrogenation of a byproduct of the oil industry apparently prevented detrimental effects of fat supplementation on ruminal digestion.